Medicare modernization and diffusion of endoscopy in FFS medicare - Mobley, Lee R. (Health Econ Rev, 2017)
OBJECTIVE: To examine how FFS Medicare utilization of endoscopy procedures for colorectal cancer (CRC) screening changed after implementation of the Medicare Prescription Drug, Improvement, and Modernization Act (MMA) in 2006, which provided subsidized drug coverage and expanded the geographic availability of Medicare managed care plans across the US. Data Sources/Study Setting. Using secondary data from 100% FFS Medicare enrollees, we analyzed endoscopy utilization during two intervals, 2001-2005 and 2006-2009. STUDY DESIGN: We examined change in predictors of county-level endoscopy utilization rates based on a conceptual model of market supply and demand with spillovers from managed care practices. The equations for each period were estimated jointly in a spatial lag regression model that properly accounts for both place and time effects, allowing robust assessment of changes over time. DATA COLLECTION/EXTRACTION METHODS: All Medicare FFS enrollees with both Parts A and B coverage who were age 65+, remained alive and living in the same state over the interval were included in the analyses. The later interval used a new cohort defined the same as the earlier interval. 100% Medicare denominator files were also used, providing county of address to use for county-level aggregation. The outcome variable was defined as county-level proportion of enrollees who ever used endoscopy over the interval. PRINCIPAL FINDINGS: Endoscopy utilization by FFS Medicare increased, and became more accessible across the US. Medicare managed care plan spillovers onto FFS Medicare endoscopy utilization changed over time from a significant negative (restraining) effect in the early period to no significant effect by the later period. CONCLUSIONS: The MMA eased budget constraints for seniors, making endoscopic CRC screening more affordable. The MMA policies also strengthened managed care business prospects, and enrollments in Medicare managed care escalated. The change in managed care spillover effects reflects the gradual acceptance of endoscopic CRC screening procedures, as they emerged as the gold standard during the period.